Cannabinoid Use for Pain Reduction in Spinal Cord Injuries: A Meta-Analysis of Randomized Controlled Trials - Tsai, Sung Huang Laurent; Lin, Chun-Ru; Shao, Shih-Chieh; Fang, Chao-Hua; Fu, Tsai-Sheng; Lin, Tung-Yi; Hung, Yu-Chiang (Frontiers in Pharmacology, 2022)
Background: Spinal cord injury (SCI) often involves multimodal pain control. This study aims to evaluate the efficacy and safety of cannabinoids use for the reduction of pain in SCI patients. Methods and Findings: This study followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement. We searched PubMed, EMBASE, Scopus, Cochrane, Web of Science, and ClinicalTrials.gov for relevant randomized controlled trials (RCTs) reporting the efficacy (e.g., pain relief) or safety (e.g., adverse events) of cannabinoids in patients with SCI, from inception to December 25th, 2021. The study quality and the quality of evidence were evaluated by Cochrane ROB 2.0 and the Grading of Recommendations, Assessment, Development and Evaluations system (GRADE), respectively. We used the random-effects model to perform the meta-analysis. From a total of 9,500 records, we included 5 RCTs with 431 SCI patients in the systematic review and meta-analysis. We judged all 5 of the included RCTs as being at high risk of bias. This meta-analysis indicated no significant difference in pain relief between cannabinoids and placebo in SCI patients (Mean difference of mean differences of pain scores: -5.68; 95% CI: -13.09, 1.73; p =0.13; quality of evidence: very low), but higher odds of adverse events were found in SCI patients receiving cannabinoids (odds ratio: 3.89; 95% CI: 2.11, 7.18; p<0.0001; quality of evidence: low). Conclusions: Current best evidence suggests cannabinoids may not be beneficial for pain relief in SCI patients, but they do increase the risks of adverse events, including dizziness, somnolence and dysgeusia, compared to placebo. Cannabinoids should not be regularly suggested for pain reduction in SCI patients. Update of systematic reviews and meta-analyses by integrating future RCTs is necessary to confirm these findings.